Conductometric titration method for determination of naftidrofuryl oxalate, propafenone HCl and sotalol HCl using silver nitrate - Ayad, Magda Mohamed; Abdellatef, Hisham Ezzat; Hosny, Mervat Mohamed; Sharaf, Yassmin Ahmed (European Journal of Chemistry, 2012)
A simple, precise, rapid, and low-cost conductometric method for determination of naftidrofuryl oxalate, propafenone HCl and sotalol HCl in pure form and in pharmaceutical formulations using silver nitrate has been described. The method is based on the precipitation of oxalate or chloride ions coming from the cited drugs with silver ions, yielding silver oxalate or silver chloride and the conductance of the solution is measured as a function of the volume of titrant. The studied drugs were evaluated in double distilled water in the range of 1-15 mg. Various experimental conditions were established and results obtained showed good recoveries with relative standard deviation of 0.909, 0.955 and 0.983 for naftidrofuryl, propafenone and sotalol, respectively. The proposed procedures were applied successfully to the analysis of these drugs in their pharmaceutical formulations. Results were favorably comparable to the official or reference methods.